2022
DOI: 10.3390/math10030504
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bioconvection and Chemical Reaction on Magneto—Carreau Nanofluid Flow through an Inclined Cylinder

Abstract: The present contribution focuses on heat transmission in the conjugate mixed bioconvection flow of Carreau nanofluid with swimming gyrotactic microorganisms through an inclined stretchable cylinder with variable magnetic field impact and binary chemical reaction. Additionally, the investigation involves the aspects of variable decrease or increase in heat source and non-uniform thermal conductivity. A passively controlled nanofluid pattern is used to estimate this nano-bioconvection flow case, which is believe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 45 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Few staple investigations on different non-Newtonian fluid models can be seen in Das and Chakraborty (2006), Zhao et al (2008), Zhao and Yang (2011), Zhao and Yang (2012), Zhao and Yang (2013b), Berli and Olivares (2008), Berli (2010), Turkyilmazoglu (2022), Othman et al (2019), Riaz et al (2021a), Zhang et al (2021), Goodarzi et al (2020), Turkyilmazoglu (2019), Saffarian et al (2020), Ellahi et al (2019), Awan et al (2022), Ellahi (2013) and Elelamy et al (2020); however, a hybrid model for non-Newtonian fluids in the said studies is more general form of the Carreau non-Newtonian model. At low and intermediate shear rate, a Carreau fluid behaves as a Newtonian and power law fluid, respectively (Alqarni et al , 2022; Riaz and Sadiq, 2020; Nabwey et al , 2022a; Jalali et al , 2020). Compared to Newtonian fluids, Carreau hybrid model contains five extra parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Few staple investigations on different non-Newtonian fluid models can be seen in Das and Chakraborty (2006), Zhao et al (2008), Zhao and Yang (2011), Zhao and Yang (2012), Zhao and Yang (2013b), Berli and Olivares (2008), Berli (2010), Turkyilmazoglu (2022), Othman et al (2019), Riaz et al (2021a), Zhang et al (2021), Goodarzi et al (2020), Turkyilmazoglu (2019), Saffarian et al (2020), Ellahi et al (2019), Awan et al (2022), Ellahi (2013) and Elelamy et al (2020); however, a hybrid model for non-Newtonian fluids in the said studies is more general form of the Carreau non-Newtonian model. At low and intermediate shear rate, a Carreau fluid behaves as a Newtonian and power law fluid, respectively (Alqarni et al , 2022; Riaz and Sadiq, 2020; Nabwey et al , 2022a; Jalali et al , 2020). Compared to Newtonian fluids, Carreau hybrid model contains five extra parameters.…”
Section: Introductionmentioning
confidence: 99%
“…From their conclusions, they observed that the liquid velocity becomes lower for a larger viscosity parameter. Nabwey et al 2 have offered the effect of non-Newtonian liquid flow with motile microorganisms by using the bvp4c technique over an inclined stretching cylinder. In this evaluation, it is detected that the increment in curvature parameter, enhanced the value of absolute drag force.…”
Section: Introductionmentioning
confidence: 99%
“…Sohail et al (2022) studied three kinds of mass species in Carreau liquid in the presence of activation energy over a stretching plate. Nabwey et al (2022) investigated the thermal aspects of Carreau nanofluid taking into account the chemical species and bioconvection in a cylinder. Reedy et al (2022) discussed a model for a Carreau fluid including entropy generation over a heated microchannel.…”
Section: Introductionmentioning
confidence: 99%